How to deal with global concept of Risk in Agriculture? Comparative overview of the literature - Bencová Tatiana; Boháčiková Andrea (SHS Web of Conferences, 2021)
Research background: Risk is an important aspect of the agriculture business. The uncertainties inherent in the changes in input and output prices, climate and biological variables, agricultural policies and government decisions, global markets and the volatility, sales, world trends in the consumption, environmental legislation and other factors that impact agriculture can cause big differences in farm production and in general in farm income. Purpose of the article: The aim of the paper is twofold. The first task is to survey and classify the main types of risks in agriculture, risk evaluation methods, approaches for estimation and to present the applications of these methods across the literature. The second aim is to point out how to measure the risk in agriculture enterprises. Methods: In the recent years, there was an increase in the number of risk studies with potential to further deepen and develop the previous studies. This study provides a literature overview of risk studies in agriculture. More specifically, this paper discusses the sources of risk in agriculture, summarizes the literature and methods of measuring the risk and comments the problems with risk evaluation in agriculture. Findings & Value added: The objective of this paper is to provide the methodological conclusions for further research about risks in agriculture and opportunities of risk evaluation. This review is expected to prompt researchers to perform new theoretical studies and stimulate to analyse and measure risks in agriculture.